EDUKASI EDUKASI KEGAWATAN PADA KEHAMILAN LANJUT DI MASYARAKAT - Murbiah, Murbiah; Salsabila, Nabila; Safitri, Meilia Safitri (Institut Citra Internasional, 2025)
Pregnancy is a physiological process experienced by a woman in her reproductive journey. However, not all pregnancies go smoothly. Data from the World Health Organization (WHO) shows that complications of pregnancy and childbirth are one of the leading causes of maternal death worldwide. In 2023, WHO noted that around 295,000 women died from complications of pregnancy and childbirth, mostly in developing countries. One of the main factors causing the high rate of pregnancy complications is the lack of knowledge of pregnant women and their families regarding the signs of emergency in advanced pregnancy. Education regarding emergency pregnancy conditions is very much needed to increase the awareness and preparedness of pregnant women and their families in facing possible risks. The use of educational media such as leaflets in the antenatal care (ANC) program is a strategic step to increase awareness of pregnant women, detect complications early, and reduce maternal and infant mortality rates. Objective to increase the knowledge of pregnant women about emergency pregnancy further. Method Health Education to increase knowledge by implementing Health counseling for pregnant women using leaflets and questionnaires on knowledge about emergency pregnancy further to measure the increase in knowledge. The average value of pregnant women's knowledge before being given education with leaflet media about advanced pregnancy emergencies was 36.75, the average value of pregnant women's knowledge after being given education with leaflet media about advanced pregnancy emergencies was 80.25. There was an increase in pregnant women's knowledge after further education about pregnancy emergencies was given.